1998
DOI: 10.1080/09540109809354989
|View full text |Cite
|
Sign up to set email alerts
|

Antigenically stable 35 kDa outer membrane protein ofSalmonella

Abstract: Outer membrane protein (OMP) extracts from Salmonella species representing seven serogroups were examined by SDS-PAGE followed by immunoblotting. Two major proteins with apparent molecular weight of 24 and 35 kDa were identified. The latter protein was present only in Salmonella. Immunoblotting with a monoclonal antibody (MAb) 1D6 (IgA) demonstrated the 35 kDa OMP contains an antigen common for all tested Salmonella species with the exception of atypical species such as S. arizona. The type of growth media had… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
3
0

Year Published

2001
2001
2017
2017

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 20 publications
2
3
0
Order By: Relevance
“…The specificity of the monoclonal antibodies was further tested using SDS-PAGE and immunoblotting. The SDS-PAGE protein profiles for the OMPs observed in this study were similar to those of OMPs described by other researchers for other members of the Enterobacteriaceae [38,39]. Overall, most of the isolates contained OMP proteins with MW ranged from 34-55 kDa (Figure 2 upper panel) with majority of the isolates exhibiting proteins in the range of 36-49 kDa with the 49 kDa protein appeared in all Cronobacter species (Figure 2 upper panel).…”
Section: Discussionsupporting
confidence: 88%
“…The specificity of the monoclonal antibodies was further tested using SDS-PAGE and immunoblotting. The SDS-PAGE protein profiles for the OMPs observed in this study were similar to those of OMPs described by other researchers for other members of the Enterobacteriaceae [38,39]. Overall, most of the isolates contained OMP proteins with MW ranged from 34-55 kDa (Figure 2 upper panel) with majority of the isolates exhibiting proteins in the range of 36-49 kDa with the 49 kDa protein appeared in all Cronobacter species (Figure 2 upper panel).…”
Section: Discussionsupporting
confidence: 88%
“…Nearly similar results were obtained by El-Reedy et al (2007) who identified about 12 different protein bands ranging from 22-289 KD by SDS-PAGE analysis of 12 different salmonella serotypes isolated from poultry. Also there were common protein bands at 15, 26 and 35 KD identified in all isolated Salmonella serovars which agreed with the results obtained by Ames (1973), Sarasombath et al (1988) and Joradat and Zawistowski (1998) who detected the presence of 35 KD protein band in all examined salmonellae. On the other hand, S. cerro was characterized by 3 deeply stained protein bands at 120, 60.15 and 26 KD.…”
Section: Discussionsupporting
confidence: 91%
“…SDS-PAGE revealed that the band of size ~29kDa, which was shared by the four highly invasive C. malonaticus strains, was flagellin (FliC) (Figure 4 , Table 4 ). The flagellin (FliC) is a major protein of bacterial flagella, which has been shown to have a crucial role in adhesion and invasion of pathogenic bacteria (Hofstra et al, 1980 ; Jaradat and Zawistowski, 1998 ; Haiko and Westerlund-Wikström, 2013 ). The same protein band of 29kD was previously detected and identified as flagelin in five different Cronobacter species using anti-flagella antibody coupled with mass spectrophotometry (Cruz-Córdova et al, 2012 ).…”
Section: Discussionmentioning
confidence: 99%